Growth and relations between auxology, caregiving environment and cognition in socially deprived Romanian children randomized to foster vs. ongoing institutional care - Johnson, Dana E. (2010)
OBJECTIVE: To determine the effects of improved nurture compared with institutional care on physical growth and the relations between growth and cognitive development. DESIGN: A randomized controlled trial beginning at baseline (mean 21.0, range 5.4–32 months) with follow-up at 30, 42 and 54 months of age. SETTING: Institutionalized and community children in Bucharest, Romania PARTICIPANTS: 136 institutionalized though otherwise healthy children from six orphanages and 72 typically developing, never-institutionalized children. INTERVENTION: Institutionalized children were randomly assigned to foster care or to receive institutional care as usual. OUTCOME MEASURES: Auxology and measures of intelligence over time. RESULTS: Growth in institutionalized children was compromised, particularly in infants <2,500 grams. Mean height and weight, though not head size, increased to near normal within 12 months in foster care. Significant independent predictors for greater catch-up in height and weight included age <12 months at randomization and higher caregiving quality, particularly caregiver sensitivity and positive regard. At 54 months, birth weight < 2500 grams was associated with a 11.0±3.7(standard error) point lower IQ and each incremental increase of one in standardized height scores between baseline and 42 months was associated with a 6.2±3.0 point increase in IQ (p<.05). CONCLUSIONS: Foster care had a significant effect on growth particularly with early placement and high quality care. Growth and IQ in low birth weight children are particularly vulnerable to social deprivation. Catch-up growth in height under more nurturing conditions is a useful correlate of caregiving quality and cognitive abilities. TRIAL REGISTRATION: clinicaltrials.gov Identifier: NCT00747396